Pengaruh Leverage dan Profitabilitas terhadap Volatilitas Harga Saham dengan Kebijakan Dividen sebagai Variabel Intervening Sebelum dan Selama Covid-19 - Kadek Mikra Anila W; Titik Inayati; Fatia Fatimah (Owner : Riset dan Jurnal Akuntansi, 2023)
During the Covid-19 pandemic, business conditions around the world were very unstable. Various business sectors are experiencing difficulties due to social distancing regulations, supply chain pressures, economic instability, and so on. Therefore this study reviews the effect of financial performance (leverage and profitability) on stock price volatility with dividend policy as an intervening variable. This research is focused on seeing the impact of the pandemic on the business world and the management's response to all these uncertainties. The population in this study are LQ45 companies listed on the Indonesia Stock Exchange in the 2018 - 2020 period, so there are 45 companies in the population. These samples were taken using a purposive sampling method. The results of this study indicate that leverage has a direct effect on dividend policy and stock price volatility. The leverage variable also has an indirect effect on stock price volatility through dividend policy. However, profitability does not have a direct or indirect effect on stock price volatility and dividend policy. Based on the Sobel test, it was known that Covid-19 has no effect on the value of leverage, dividend policy and stock price volatility, except profitability.